Does maternal underweight prior to conception influence pregnancy risks and outcome? - Hoellen, Friederike; Hornemann, Amadeus; Haertel, Christoph; Reh, Annette; Rody, Achim; Schneider, Sven; Tuschy, Benjamin; Bohlmann, Michael K. (In vivo, 2014)
AIM: Data analyzing risks during pregnancy and neonatal outcome in Caucasian women with pre-conceptional underweight are scarce. - PATIENTS AND METHODS: We conducted a retrospective cohort study in Northern Germany comparing pregnancy risks and neonatal outcomes in nulliparous women with either pre-conceptional underweight or normal weight. - RESULTS: The data of 3,854 nulliparous women with either underweight (n = 243; BMI ≤ 18.5 kg/m(2)) or normal weight (n = 3611; BMI 18.5-24.9 kg/m(2)) were screened. The risks for preterm birth (23.3 vs. 18.6%; p = 0.004) and neonatal underweight were significantly higher in women with underweight prior to conception (p < 0.0001). The risk for secondary caesarean sections was significantly lower in underweight patients. - CONCLUSION: To our knowledge, the present retrospective cohort study constitutes the largest sub-group analysis on delivery and maternal and neonatal outcome in pre-conceptionally underweight mothers. There are significantly more preterm deliveries in underweight mothers, while maternal outcome and birth-associated trauma (lacerations, caesarean section) is not disadvantageously influenced by maternal underweight. Further investigations are required in order to specify nutritional deficits in underweight pregnant women and to optimize medication in cases where nutritional balance cannot be achieved in order to improve the neonatal status at birth.